Kajian Teknis Produksi Alat Gali-Muat dan Angkut pada Penambangan Batu Gamping PT Akarna Marindo di Desa Cipatat Kecamatan Cipatat, Kabupaten Bandung Barat, Provinsi Jawa Barat - Arrmandha Alghifari; Iswandaru; Elfida Moralista (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Limestone mining activities at PT Akarna Marindo include digging-loading and hauling activities, this activity is very important in mining activities because it involves achieving production targets. The problem in this study was not achieving the production target of 20,000 tons/month, because of this a technical study was carried out on loading and hauling equipment aimed at calculating actual production, knowing the factors that influence actual production, knowing match factors, and knowing efforts to increase production. The research was conducted in the mining area at location A, by observing the activities of digging, loading and transporting 1 Excavator PC-200 and 2 DT Hino FM 260 JD. The data collected is primary data including road geometry, number of digging-loading and hauling equipment, productive work time, cycle time of digging-loading and hauling equipment, inhibition time, in-situ density, loose density, swell factor and fill factor. Secondary data includes production targets, administrative maps, topography, geology, annual rainfall, specifications for digging and hauling equipment. Production of digging and loading equipment is 13.605,9 tons/month and transportation equipment is 13.521,1 tons/month, with an MF value of 0.83 (MF < 1). The production results did not reach the production target of 20,000 tons/month, the reasons for not achieving the production target were due to time constraints, not ideal road geometry, and less than optimal speed of the conveyance. Because of this, improvements were made to the road geometry, work efficiency and the cycle time of the transportation equipment, the results of the improvements were able to increase the production of the transportation equipment to 20.208,75 tons/month. Abstrak. Kegiatan penambangan batu gamping di PT Akarna Marindo meliputi aktivitas gali-muat dan angkut, aktivitas ini merupakan hal yang sangat penting dalam kegiatan penambangan karena menyangkut ketercapaian target produksi. Permasalahan dalam penelitian ini adalah tidak tercapainya target produksi sebesar 20.000 ton/bulan, karena itu dilakukan kajian secara teknis alat-gali muat dan angkut bertujuan untuk menghitung produksi aktual, mengetahui faktor-faktor yang memengaruhi produksi aktual, mengetahui match factor, dan mengetahui upaya untuk meningkatkan produksi. Penelitian dilakukan pada area penambangan lokasi A, dengan mengamati aktivitas penggalian, pemuatan dan pengangkutan 1 alat gali-muat Excavator PC-200 dan 2 alat angkut DT Hino FM 260 JD. Data yang dikumpulkan adalah data primer meliputi geometri jalan, jumlah alat gali-muat dan angkut, waktu kerja produktif, waktu edar alat gali-muat dan angkut, waktu hambatan, density insitu, density loose, swell factor dan fill factor. Data sekunder meliputi target produksi, peta administrasi, topografi, geologi, curah hujan tahunan, spesifikasi alat gali-muat dan angkut. Produksi alat gali-muat 13.605,9 ton/bulan dan alat angkut 13.521,1 ton/bulan, dengan nilai MF sebesar 0,83 (MF < 1). Hasil produksi tersebut tidak mencapai target produksi 20.000 ton/bulan, penyebab tidak tercapainya target produksi karena adanya waktu hambatan, geometri jalan tidak ideal, dan kurang optimalnya kecepatan alat angkut. Oleh karena itu dilakukan perbaikan geometri jalan, efisiensi kerja dan cycle time alat angkut, hasil perbaikan mampu meningkatkan produksi alat angkut menjadi 20.208,75 ton/bulan.